2014
DOI: 10.4038/kjm.v2i2.6548
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and union citizenship behavior: Are they unilateral or multilateral in Sri Lankan public sector context

Abstract: Empirical studies on citizenship behavior of employees are largely centered on organizational citizenship behavior of employees. Other form of citizenship behavior of employees such as union citizenship has been identified. However, studies on citizenship behavior with a multilateral perspective are scant in behavioral studies and in Sri Lankan context in particular. The objective of this study is to examine whether organizational and union citizenship behavior are exhibited simultaneously by unionized employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…So that the leaders of apparel sector manufacturing organizations always look for new strategies which drives the companies to as competitive edge. According to Dhammika (2013) managers of the Sri Lankan organizations deliberately develop HR strategies to enhance the OCB of the employees.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…So that the leaders of apparel sector manufacturing organizations always look for new strategies which drives the companies to as competitive edge. According to Dhammika (2013) managers of the Sri Lankan organizations deliberately develop HR strategies to enhance the OCB of the employees.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Also it was identified that strategies such as HR practices, job embebdedness and employee engagement can be used to promote OCB in an organization. Same as in the Sri Lankan context managers deliberately develop human resource management strategies in a way that develops the OCB of employees in their organizations (Dhammika, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It claims that there would be dual citizenship behavior of unionized employees (Dhammika, 2014). That is employees may exhibit citizenship behavior towards both the organization and union.…”
Section: Organizational Citizenship Behavior (Ocb) and Unionizationmentioning
confidence: 99%